Smart material interfaces for education. (December 2015) - Minuto, Andrea; Pittarello, Fabio; Nijholt, Anton
Abstract: This paper describes an experience, held with a class of primary school children, aimed to introduce a novel educational topic, the smart materials, and the interfaces built with them (Smart Material Interfaces). The pupils were guided along a multidisciplinary path in which traditional and innovative teaching methods were composed for educating while engaging the children. It led to the creation of 6 automated puppet plays focused on the themes of environmental awareness as a result. In this process, storytelling and visual programming acted as powerful means for merging different educational concepts and techniques. The data collected through the direct observation and the questionnaires indicate that the experience was perceived as positive and interesting. The post evaluation, held some months later, revealed skills and knowledge improvements in all the areas involved by the multidisciplinary experience. Abstract : Highlights: Teaching children through smart materials, Scratch, Arduino and origami. Smart origami models tell a story. Engaging scientific education.